Aturan Penggunaan Smartphone bagi Mahasiswa dalam Tinjauan Kaidah Sadd al-Żarī’ah (Studi Kasus Asrama Putra STIBA Makassar): Rules for Smartphone Use Among Students in the Perspective of the Uṣūl Fiqh Principle of Sadd Al-Żarī’ah (Case Study at the Male Dormitory of STIBA Makassar) - Ariesman M.; Syandri, Syandri; Dwi Faturrahman (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This research aims to examine the practices regarding the implementation of smartphone usage rules among university students through the perspective of the uṣūl fikih principle of sadd Al-Żarī’ah at the Male Dormitory of STIBA Makassar by identifying two research questions: how the smartphone usage rules are applied within the dormitory environment and how the uṣūl fikih principle is evaluated in the context of the existing regulations. The study employs a qualitative approach using field research design that integrates normative, uṣūl fikih, case, and psychological approaches, with primary data obtained through interviews and secondary data sourced from the Qur’an, hadith, scholarly texts, academic journals, and the internet. The findings indicate that the smartphone usage regulations at the dormitory have been codified in a student handbook and classified into three categories, namely, usage permitted under certain conditions, usage subject to restrictions, and usage absolutely prohibited, with three main types of violations identified: dissatisfaction and protests against the rules, covert and excessive usage, and serious breaches of religious law. The application of the uṣūl fikih principle of sadd Al-Żarī’ah is deemed appropriate based on the principle of maslahat, considering that STIBA is an institution with a dormitory system where all students are required to live together, thereby necessitating strict regulations to prevent declines in academic performance, moral standards, and ethical conduct. The implications of this research are expected to serve as an important reference for the development of literature and policies in the educational sector, particularly for boarding schools or dormitory-based universities such as STIBA Makassar, as well as to provide a positive contribution as a source of information for academics and the general public.